The Effectiveness of Code Switching in Denny Sumargo Podcast: Cinta Laura Terjebak Toxic Relationship - Anzani, Wika Putri; Pangestu, Maulani; Buansari, Istihayyu (Pujangga : Jurnal Bahasa dan Sastra, 2024)
Code switching is a combination of two or more languages and a combination of words, phrases and sentences. Code switching is usually used by bilinguals or multilinguals. This research aims to examine the types of code switching and determine the effectiveness of using code switching to find out how far respondents understand the use of code switching that occurs in Denny Sumargo's video podcast with Cinta Laura by using a questionnaire to 30 respondents. This research was conducted using mixed methods, namely qualitative methods and quantitative methods. In this research, there are 3 types of code switching according to Poplack (1980), namely Intra-sentential switching, Inter-sentential switching and Tag switching. And the results show that intra-sentential switching is the most dominant type of code switching that occurs. From that the use of code switching, it was found that 43% of respondents agreed with positive statements and 29% of respondents disagreed with negative statements. So it can be concluded that the effectiveness of using code switching in the video podcast content is quite effective and can be well understood by the majority of respondents.